Professional Training of Future Masters – Teachers of Ukrainian Language and Literature: Purpose, Tasks, Structure - Valentyna Kryshchuk; Liudmyla Pavlishena; Bogdan Kryshchuk (Pedagogical Discourse, 2024)
The peculiarities of professional training of future teachers of the Ukrainian language and literature at the stage of Ukraine's integration into the unified European educational space have been elucidated, the main elements of the structure of training of the applicants for the second (master's) degree of higher education have been presented in the article. The works of scientists and legislative documents on the investigated problem has been analyzed. The attention has been drawn to the fact that the informational and content, psychological and pedagogical, methodological and technological support of the educational process affects the effectiveness of the formation of professional competencies of future masters. The contradictions that arise in the process of training masters have been outlined and characterized and the ways to overcome them have been presented. The following general scientific methods have been used to implement the purpose and objectives of the article: analysis, synthesis, induction and deduction, systematization and generalization, analysis of literary sources, regulations and legal acts, and comparative analysis. The purpose, goals, orientation and emphasis of the educational and professional program “Secondary Education (Ukrainian Language and Literature)” of the second (master's) degree of higher education in the specialty 014.01 Secondary Education (Ukrainian Language and Literature), which is implemented in the educational process of Khmelnytskyi Humanitarian and Pedagogical Academy, have been revealed. The general and professional competencies, which are provided by the educational and professional program, have been highlighted. The basic principles of organizing the training of masters of Ukrainian language and literature based on the analysis of the curriculum and the educational program have been determined, the list of educational components and the volume of the program in ECTS credits have been presented. Various aspects of the professional training of lexicography teachers have been studied: teaching and educative activities, organization of research and independent work, conducting various types of practice. The content and main tasks of educational and industrial practice have been clarified, the peculiarities of organizing the independent work of master's students, its types, forms, principles and optimal conditions for the qualitative performing of assigned tasks have been analyzed. Emphasis is placed on an integral component of training highly qualified teachers of Ukrainian language and literature – the performance of qualification (master's) thesis (on a current problem of the educational sphere); the purpose, tasks and requirements for the procedure for defending qualification works have been clarified. The necessity on expanding the boundaries of philological knowledge and familiarizing future teachers of Ukrainian language and literature with new linguistic and literary studies have been emphasized. The author's vision of the modern training of future lexicography teachers is based on the introducing of a competency-based approach to teaching master's students. In order to implementing the main task of the educational and professional program – training of highly qualified teachers of the Ukrainian language and literature – the key competencies have been identified: social and personal, general scientific, instrumental, professional. Future research in this direction covers various aspects of the content component of professional training of future teachers of Ukrainian language and literature, as well as the identification and research of the most optimal methods, techniques and forms of performing various types of educational, educative, researching and independent work of master's students.